Anxiety and Performance in Sex, Sport, and Stage: Identifying Common Ground - Rowland, David L.; van Lankveld, Jacques J. D. M. (Frontiers in Psychology, 2019)
Anxiety has long been associated with diminished performance within a number of domains involving evaluative interpersonal interactions, including Sex, Sport, and Stage. Here we pose three questions: (1) how do these disparate fields approach and understand anxiety and performance; (2) how does the understanding of the issue within one field offer insight to another field; and (3) how could each field benefit from the ideas and strategies used by the others. We begin with a short review of models of anxiety/arousal and performance and then explore definitions, models, presumed underlying physiological processes, and characterizing and influencing factors within each domain separately in a narrative review. This discussion is followed by a synthesis that identifies elements specific to and common across the various domains, with the latter captured in a model of essential characteristics. Concluding remarks note the potential value of promoting increased cross-disciplinary conversation and research, with each domain likely benefiting from the conceptualizations and expert knowledge of the others.